ANALISIS KUALITAS AIR SUNGAI METRO BERDASARKAN PARAMETER FISIK DAN DERAJAT KEASAMAN (pH) - Meviana, Ika; Kurniawati, Dwi; Tri Murni Darmon, Agustina (Geography Education Study Program, Faculty of Teacher Training and Education, 2024)
Every production process will produce waste, especially liquid waste. This liquid waste requires special attention in industrial control efforts because the waste after liquid waste treatment will be flowed into water bodies. The purpose of this research is to analyze the water quality of Metro river based on physical parameters and acidity (pH). This research is a descriptive survey research. The research sample consists of Metro river water flow Pakisaji District Malang Regency which consists of 3 points namely in the up stream, middle stream, down stream. Sampling technique with grab sample method and examination with measurement using wather checker tool. The data obtained were analyzed by descriptive method. Based on the results of research and laboratory tests, it is known that the status of Metro river water quality based on physical parameters and the degree of acidity is still classified as mildly polluted and good condition. It is suggested that business owners who take part in discharging waste into the Metro river should participate in maintaining the sustainability of the river by not discharging industrial waste into the river.